Corporate debt structure over the global credit cycle - Nina Boyarchenko; Leonardo Elias (Federal Reserve Bank of New York, 2024)
We study the determinants of active debt management through issuance and refinancing decisions for firms around the world. We leverage instrument-level data to create a comprehensive picture of the maturity, currency, and security type composition of firms' debt for a large cross-section of countries. At the instrument level, we estimate a predictive model of prepayment as a function of interest costs savings and maturity lengthening motives. We document that there is substantial heterogeneity in prepayment across bonds and loans and across firms, depending on their reliance on bank lending. While debt prepayment is generally successful at extending average maturities and lowering interest rate costs at the firm level, these benefits appear smaller for issuers in emerging market economies. Tight global credit conditions reduce both the ability to prepay debt early and the effectiveness of debt refinancing in reducing interest costs and rollover risk. Put together, our results show that the impact of global credit conditions on firms' debt structure can be traced back to how instrument-level prepayment incentives change over the global credit cycle.
Keywords: G32; G15; F30; F44; 330; debt structure; active debt management; global credit cycle; prepayment